Pemanfaatan Media Promosi sebagai Sarana Pemasaran Pariwisata Festival Budaya Peh Cun di Kota Tangerang Tahun 2024 - Oksapianus, David Soni; Hardiyanti, Rini; Suseno, Ari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The Peh Cun Festival is one of the cultural traditions brought by ethnic Chinese who came to Indonesia, the Cisadane River Peh Cun Festival itself is one of the oldest festivals in Indonesia. This festival is one of the big and lively cultural tourism agendas because there are various interesting event activities presented, the Peh Cun media can be said to be lacking in terms of promotion, especially in promotion using existing digital media. So, promotions need to be carried out to increase the number of tourist visits. This study aims to determine how to utilize effective Promotional Media in Marketing the Peh Cun Cultural Festival in Tangerang City. This study uses a qualitative descriptive method, with data collection techniques using interviews, observations and documentation. The results of the study show that the Tourism Communication used by the Boen Tek Bio Association in promoting the 2024 Peh Cun Festival includes Integrated Marketing Communication (IMC). This implementation can be seen from the use of Print Media, Outdoor Media, Electronic Media and Content on Social Media. Inhibiting factors in the 2024 Peh Cun Festival activities are time constraints and natural factors, while supporting factors include full support from the City Government, local television and radio stations, surrounding communities, and the local community.